Design, kinematic modeling and evaluation of a novel soft prosthetic hand with abduction joints - Yadong Yan; Xiangqian Chen; Chang Cheng; Yu Wang (Medicine in Novel Technology and Devices, 2022)
This paper presents a novel tendon-driven soft prosthetic hand with 5 fingers and 9 independent actuators. A special notched structure was used as the finger joint, which brings adequate compliance to grasping. The soft finger has two kinds of vertically arranged joints that can produce flexion/extension and abduction/adduction motions under tension and release, enabling a three-dimensional workspace of the finger and improving the dexterity of the hand. The design and manufacture of the finger and soft hand are described in detail. An open-loop kinematic model based on piecewise constant curvature of the finger was established and verified experimentally. The results show that the model could precisely predict finger movement. The slip resistance of the soft hand was tested, and the capacity to grasp objects was evaluated based on power grasp and precision grasp. With abduction joints, the proposed hand can perform various gestures and in-hand manipulations, which indicate high dexterity. This work provides a way to realize high dexterity for soft prosthetic hands.